"Now you're connected": Carceral visuality and police power on MobilePatrol. (May 2020) - Revier, Kevin
Police increasingly rely on new media software for public communication and policing operations. One such software is MobilePatrol: Public Safety App, a free to use mobile phone application marketed by data and analytics company Appriss Safety. It compiles information including mug shot photos, sex offender lists, and most wanted profiles for public access. To capture carceral visuality on the application, I conduct an ethnographic content analysis of police use in upstate New York. I penned a daily user log, took in-app "screenshots", and analyzed user product reviews. I find that MobilePatrol reinforces an emerging new carceral visibility where an assemblage of police records are rapidly disseminated for widespread consumption, further driving data-led state entrenchment into the public sphere.